2013
DOI: 10.1103/physrevb.87.014103
|View full text |Cite
|
Sign up to set email alerts
|

Calculations of isothermal elastic constants in the phase-field crystal model

Abstract: The phase-field crystal (PFC) method is an emerging coarse-grained atomistic model that can be used to predict material properties. In this work, we describe procedures for calculating isothermal elastic constants using the PFC method. We find that the conventional procedure used in the PFC method for calculating the elastic constants are inconsistent with those defined from a theory of thermoelasticity of stressed materials. Therefore, we present an alternative procedure for calculating the elastic constants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 44 publications
4
40
0
Order By: Relevance
“…We believe the addition of atoms into the system as σ increases is the cause for a decreasing solid-liquid interfacial energy, which is in disagreement with the trend measured experimentally [25,26] and calculated using atomistic simulations [27][28][29] for closed systems. In order to directly compare the dependence of γ p (σ, α 0 , α 0 ) on σ from the PFC model to the dependence of γ p (σ, α 0 , α 0 ) on melting temperature from experiments and atomistic simulations, it is required to keep the number of particles constant as σ is varied, which is similar to what has been implemented for calculating elastic constants [30].…”
Section: B Solid-liquid Interfacial Energy Dependence On the Peak-widthmentioning
confidence: 99%
“…We believe the addition of atoms into the system as σ increases is the cause for a decreasing solid-liquid interfacial energy, which is in disagreement with the trend measured experimentally [25,26] and calculated using atomistic simulations [27][28][29] for closed systems. In order to directly compare the dependence of γ p (σ, α 0 , α 0 ) on σ from the PFC model to the dependence of γ p (σ, α 0 , α 0 ) on melting temperature from experiments and atomistic simulations, it is required to keep the number of particles constant as σ is varied, which is similar to what has been implemented for calculating elastic constants [30].…”
Section: B Solid-liquid Interfacial Energy Dependence On the Peak-widthmentioning
confidence: 99%
“…The above-mentioned PFC model is also called one-mode PFC, because it damps the dynamics of the system except near the first density wave length. Examples of different applications of PFC models include simulating solidification [6], elastic deformation [7], spinodal decomposition [8], grain-boundary premelting [9], dislocation dynamics [10], Kirkendall effect [11], structural phase transformation [12,13], and stacking faults [14]. PFC models can be also used in quantitative modeling of materials if its model parameters are determined for the material of interest at a given temperature; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it can represent (by only minimizing the free energy) principal RLVs with closed triangle forms, which are hexagonal and BCC structures in two-dimensional (2D) and three-dimensional (3D) spaces, respectively [9]. The one-mode PFC model is already applied to study different phenomena in materials science, including solidification [10], elastic deformation [11], spinoidal decomposition [12], grain boundary premelting [13], dislocation dynamics [14], and Kirkendall effect [15]. Furthermore, it was shown that the one-mode PFC model can be used to quantitatively simulate the two-phase solid-liquid coexistence of Fe [16][17][18] by determining its model parameters from molecular dynamics (MD) simulations.…”
Section: Introductionmentioning
confidence: 99%